High‐molecular‐weight poly(Gly‐Val‐Gly‐Val‐Pro) synthesis through microwave irradiation. (July 2016) - Goto, Mitsuaki; Endo, Takeshi
Abstract : In this study, we synthesized a polypeptide from its pentapeptide unit using microwave irradiation. Effective methods for polypeptide synthesis from unit peptides have not been reported. Here, we used a key elastin peptide, H‐GlyValGlyValPro‐OH (GVGVP), as the monomer peptide. It is difficult to obtain poly(Gly‐Val‐Gly‐Val‐Pro) (poly(GVGVP)) from the pentapeptide unit of elastin, GVGVP, via polycondensation. Poly(GVGVP) prepared from genetically recombinant Escherichia coli is a well‐known temperature‐sensitive polypeptide, and this temperature sensitivity is known as the lower critical solution temperature. When microwave irradiation was performed in the presence of various additives, the pentapeptide (GVGVP) polycondensation reaction proceeded smoothly, resulting in a product with a high molecular weight in a relatively good yield. The reaction conditions, like microwave irradiation, coupling agents, and solvents, were optimized to increase the reaction efficiency. The product exhibited a molecular weight greater than Mr 7000. Further, the product could be synthesized on a gram scale. The synthesized polypeptide exhibited a temperature sensitivity that was similar to that of poly(GVGVP) prepared from genetically recombinant E. coli . Therefore, this technique offers a facile and quick approach to prepare polypeptides in large amounts. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Abstract : The use of microwave irradiation for the polycondensation of peptides is a unique way to synthesize polypeptides. The obtained polypeptide exhibited temperature sensitivity similar to that of polyGVGVP prepared from genetically recombinant Escherichia coli . This technique only requires microwave radiation and can yield the desired polypeptide in large amounts in only a few minutes.